Physical Activity and Dietary Protein Intake as Determinants of Nutritional Status in Undernourished Toddlers: A Cross-Sectional Study in Rural Indonesia - Solo, Rosalia Astria Tanggu; Indasah, Indasah; Ambarika, Rahmania (Health and Technology Journal (HTechJ), 2026)
The first five years of life represent a critical developmental window that requires optimal nutrition and lifestyle inputs. Despite global health advancements, childhood undernutrition remains highly prevalent in rural Indonesia, exacerbated by inadequate dietary practices and unregulated physical exertion. This study investigates the simultaneous effects of physical activity levels and dietary protein intake on the nutritional status of toddlers aged 2-5 years in Weebaghe Village, East Nusa Tenggara. A quantitative cross-sectional design was employed, involving 99 toddlers selected from three community health posts. Multiple linear regression analysis was used to evaluate the relationships between the independent variables and the dependent variable, nutritional status, at a significance level of p < 0.05. The analysis revealed that both physical activity (p = 0.002) and protein intake (p = 0.041) significantly influence nutritional outcomes. Both variables exhibited an inverse relationship with nutritional status, indicating that higher physical exertion without adequate caloric compensation and excessive protein consumption independently predict poorer nutritional profiles in this undernourished cohort. These findings challenge conventional assumptions, highlighting that increased physical activity and excessive protein intake can detrimentally impact toddlers in resource-constrained settings. Public health interventions must prioritize balanced energy and macronutrient distributions tailored to the specific metabolic demands of malnourished children to prevent further deterioration in growth.